Bridging the Gap: School inspection for school improvement, the leadership role. - Barbour, Dareen (2016)
With the increase trend of using school inspection as a tool for measuring school performance, it is only fair to argue that this tool should be effectively used as a mean for school improvement. As the research evidence on the effect of school inspection on school improvement continues to be controversial, and with the negative views associated with the quality of school inspection in UAE, this research aims to explore the role that school leadership plays in ensuring that the results of school inspection are properly used for school improvement. This study sought to examine the effect of reflective feedback as a moderator between school inspection and school improvement, explore teacher’s views on being an efficient asset in the school improvement plan committee, and investigate the role of school leadership in establishing a compatible and supportive work environment to its teachers. The study was profoundly based on a mixed methodology research in which four different data collection methods (questionnaire, interview, focus group, and data analysis) were deployed. Population of the study included 1 principal, 74 teachers, and 6 head of departments. Findings from this study revealed that reflective feedback on school inspection results does moderate the relationship between school inspection and school improvement as teachers do appreciate being part of the decision-making process and feel more accountable in the process.